2015
DOI: 10.1016/j.ecresq.2014.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Inequities in access to quality early care and education: Associations with funding and community context

Abstract: The purpose of the current study was to examine program-and community-level characteristics related to total points earned by early care and education programs in North Carolina's Tiered Quality Rating and Improvement System (TQRIS). Multiple statewide data sources, programand community-level characteristics were combined to better understand associations with total points awarded in the TQRIS. The concentration of state and federal funding at the program level, and the socioeconomics of the Q3 communities tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 31 publications
2
25
0
Order By: Relevance
“…This is basically a strategy of targeting childcare funding towards disadvantaged children (e.g. Hatfield et al 2015;Elango et al 2015).…”
Section: Research Questionsmentioning
confidence: 99%
“…This is basically a strategy of targeting childcare funding towards disadvantaged children (e.g. Hatfield et al 2015;Elango et al 2015).…”
Section: Research Questionsmentioning
confidence: 99%
“…In contrast, centers in the same community that received funding one standard deviation above the mean received a boost in licensing points and were of higher quality. A similar association was evident among childcare subsidy funding, community affluence, and total licensing points, with the amount of subsidy funding related to higher quality (Hatfield et al, ). Again, these findings indicate the need for equitable supports for ECE programs to support all families with young children in the United States.…”
Section: Teachers' Role In Quality Early Learning Environmentsmentioning
confidence: 68%
“…In another study (Hatfield, Lower, Cassidy, & Faldowski, ), community characteristics were examined, using census data, to assess the accessibility of high‐quality licensed ECE programs across the state of North Carolina. Results indicated that childcare centers in communities with higher percentages of disadvantage (as defined by the percent living below the poverty line, receiving public assistance, unemployed, female‐headed households with children, and Black or African American) were more likely to be of lower quality, earning fewer points in the state's Quality Rating and Improvement System (QRIS).…”
Section: Teachers' Role In Quality Early Learning Environmentsmentioning
confidence: 99%
“…The Perry Preschool Project was implemented in Michigan in the 1960s and involved 123 low-income African-American children. Of these children, 58 were randomly assigned to receive a high-quality pre-school programme as well as home visits. The Abecedarian Project was conducted in North Carolina in the 1970s with 111 predominantly African-American children in poverty.…”
Section: Participation Rates In Ecec Have Increased Recently In Oecd mentioning
confidence: 99%